2013
DOI: 10.1107/s1600536813023106
|View full text |Cite
|
Sign up to set email alerts
|

BaMnII2MnIII(PO4)3

Abstract: The title compound, barium trimanganese tris­(ortho­phosphate), was synthesized hydro­thermally. Its structure is isotypic with the lead and strontium analogues AMnII 2MnIII(PO4)3 (A = Pb, Sr). Except for two O atoms on general positions, all atoms are located on special positions. The Ba and one P atom exhibit mm2 symmetry, the MnII atom 2/m symmetry, the MnIII atom and the other P atom .2. symmetry and two O atoms are located on mirror planes. The crystal structure contains two types of chains running parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Those studies involved the synthesis and structural characterization of new phosphates such as Na 2 Co 2 Fe(PO 4 ) 3 (Bouraima et al, 2015) and Na 1.67 Zn 1.67 Fe 1.33 (PO 4 ) 3 (Khmiyas et al, 2015) belonging to the alluaudite-type structure group. In addition, divalent and trivalent transition-metal-based phosphates, such as SrNi 2 Fe(PO 4 ) 3 (Ouaatta et al, 2015) and MMn II 2 Mn III (PO 4 ) 3 (M = Pb, Sr, Ba) (Alhakmi et al, 2013a,b;Assani et al, 2013) have been shown to adopt the -CrPO 4 structure type.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Those studies involved the synthesis and structural characterization of new phosphates such as Na 2 Co 2 Fe(PO 4 ) 3 (Bouraima et al, 2015) and Na 1.67 Zn 1.67 Fe 1.33 (PO 4 ) 3 (Khmiyas et al, 2015) belonging to the alluaudite-type structure group. In addition, divalent and trivalent transition-metal-based phosphates, such as SrNi 2 Fe(PO 4 ) 3 (Ouaatta et al, 2015) and MMn II 2 Mn III (PO 4 ) 3 (M = Pb, Sr, Ba) (Alhakmi et al, 2013a,b;Assani et al, 2013) have been shown to adopt the -CrPO 4 structure type.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Notes: DNP = diffraction des neutrons sur poudre; DRXM = diffraction des rayons X sur moncristal; DRXP = diffraction des rayons X sur poudre; & = site vacant. Ré férences: (a) Glaum et al les deux exclusivement par des cations trivalents (Rittner & Glaum, 1994;Attfield et al, 1989), par une distribution statistique de cations di-et trivalents (Yahia et al, 2016;Souiwa et al, 2015b;Essehli et al, 2015), l'un par une ré partition statistique de cations di-et trivalents et l'autre uniquement par des cations di-ou trivalents (Souiwa et al, 2015a; Ben Smail & Zid, 2017b) ou l'un par des cations divalents et l'autre par des cations trivalents (Bouraima et al, 2016;Ouaatta et al, 2015;Alhakmi et al, 2013a,b;Assani et al, 2013;Korzenski et al, 1999;Hidouri et al, 2004;Kinomura et al, 1989). La derniè re ré partition cationique est observé e dans l'arsé niate objet de ce travail.…”
Section: Figureunclassified
“…In our previous hydrothermal investigations, a variety of compounds have been synthesized and characterized with different ratios of alkaline earth metal:P, viz. Sr 2 Mn 3 (HPO 4 ) 2 (PO 4 ) 2 (Khmiyas et al, 2013), BaMn II 2 Mn III (PO 4 ) 3 (Assani et al, 2013), Mg 7 (PO 4 ) 2 (HPO 4 ) 4 (Assani et al, 2011). In this context, our interest is focused on the synthesis of new iron orthophosphates with an open-framework structure.…”
Section: Chemical Contextmentioning
confidence: 99%